W.C. Fields by Himself : His Intended Autobiography with Hitherto Unpublished Letters, Notes, Scripts, and Articles. - Fields, W. C. (Taylor Trade Publishing, 2016)
Fields never got around to writing his autobiography, but at his death in 1946, he left behind a vast assortment of notes, outlines, scrapbooks, letters, scripts, scenarios, and photographs. Now his grandson, Ronald J. Fields, has edited and woven this wealth of previously unpublished material into a unique new portrait of the Great One--in his own words.